A Content Analysis of Technology-Enhanced Learning Research and Pedagogical Innovations in Senior High School Physics - Alindayu*, Robert Kevin Andaya; Bergonia, Mary Ann; Lanwang, Mary Grace (Jurnal Pendidikan Sains Indonesia, 2025)
ooo